An accomplished procedure of horseradish peroxidase immobilization for removal of acid yellow 11 in aqueous solutions - Altikatoglu Yapaoz, Melda; Attar, Azade (IWA PUBLISHING, 2020)
Horseradish peroxidase (HRP) characteristics were improved by two techniques, Na-alginate entrapment and glutaraldehyde crosslinking prior to alginate entrapment, in order to enhance the stability, functionality and removal of dyes in waste water. Free, entrapped and crosslinked-entrapped enzymes were compared by activity assays, which indicated the optimum temperature is 25 degrees C and pH 4.0-5.0. Kinetics results showed that alginate entrapment and crosslinking prior to entrapment increased V(max)and did not cause any significant decrease in K-m. The thermal resistance of the free enzyme was short-term, zero residual activity after 250 min, while the immobilized enzymes preserved more than 50% of their activity for 5 h at 60 degrees C. Immobilized HRP was resistant to methanol, ethanol, DMSO and THF. The storage stability of free HRP ended in 35 days whereas entrapped and crosslinked-entrapped HRPs had 87 and 92% residual activity at the 60th day, respectively. HRP was used in the decolorization of azo dye Acid yellow 11 and total decolorization (>99%) was obtained using crosslinked-entrapped HRP. Reusability studies presented the improvement that crosslinked-entrapped HRP reached 74% decolorization after 10 batches. The results demonstrated that the novel immobilized HRP can be used as an effective catalyst for dye degradation of industrial waste effluents.
Keywords: alginate entrapment; azo dye removal in aquatic solutions; decolorization; enzyme immobilization; glutaraldehyde crosslinking; horseradish peroxidase; FUNCTIONAL-PROPERTIES; AZO-DYE; STABILITY; IMPROVEMENT; LACCASE; ENZYME; PHENOL; Engineering; Environmental Sciences & Ecology; Water Resources